New host of Philornis deceptivus (Dodge and Aitken, 1968) (Diptera, Muscidae) in Dendrocolaptidae (Aves, Passeriformes) - Hermes Ribeiro Luz; Gonzalo Efrain Moya Borja; Ildemar Ferreira; Márcia Souto Couri (Biotemas, 2010)
Young specimens (“ninhegos”) of the Narrow-billed woodcreeper Lepidocolaptes angustirostris sustained about 67 larvae from 2005 to 2006. Larvae were observed from the 4th day after hatching. They were removed and their life cycle was accompanied. Eightheen larvae reached the adult stage. They were put into an artificial nest inside a plastic box and their life cycle was observed until hatching. As soon as the adults began dying, we preserved them in alcohol 70% for further identification. No previous information exists about L. angustirostris as a potential host for Philornis, and this work represents the first record for this species.